(3TQM bGfhf GHf SjfGs - (3eMeO Hf eMehO GdBedis; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3hHYO , ajbhd eMeO Hf eMehO GdBedi (B: (3deG JWGHbJ GdCQGA hGJab GdYbdGA Ydi Cf CTO GdYdhe s
(3BNQgG (B:s
(3bGd , djcf gPG GdbOQ ef cdGefG GdeNJUQ ai GdCUhd GdcdjI dUfGYI GdWH cGajkG s
(3cJHJ ai MjGI GdeDdas
(3cJHg dCHi ESMGb Hf Gdedc GdSYjO eMehO TGgs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdWHs